Development of learning material based on troubleshooting at aljabar linear lectures - Astri Wahyuni; Lilis Marina Angraini (Math Didactic: Jurnal Pendidikan Matematika, 2019)
This research aims to produce learning material through the Learning Obstacle analysis of mathematics education students in mathematical problem-solving skills in validated Linear Algebra courses. This type of research is research and development with 4D development model consists of 4 stages: Define, Design, Develop, Disseminate. Learning materials in this research is LKM. The subjects of this were 40 students of the Mathematics Education Program at the Islamic University of Riau in the 2019/2020 academic year. In this research, the data used were the results of the validation questionnaire trial assessed by an expert called the validator. The data obtained will be analyzed using qualitative descriptive analysis. Based on the results of the research, it can be concluded that the LKM-1 average overall validity of the validator is 70, including valid category. In LKM-2 the average validation and overall validation is 70, including valid category. In LKM-3 the average validation and overall validation is 100, including the category is very valid. And for the whole from LKM-1 to LKM-3 the average validator obtained 80 with a valid category. Overall the results of the research showed that the learning materials developed were feasible to use.